Genetic Polymorphisms and Peritoneal Membrane Function. Issue 5 (September 2015) - Siddique, Imad; Brimble, K. Scott; Walkin, Louise; Summers, Angela; Brenchley, Paul; Herrick, Sarah; Margetts, Peter J.
Background: Outcomes for peritoneal dialysis (PD) patients are affected by the characteristics of the peritoneal membrane, which may be determined by genetic variants. We carried out a systematic review of the literature to identify studies which assessed the association between genetic polymorphisms, peritoneal membrane solute transport, and clinical outcomes for PD patients. Methods: The National Library of Medicine was searched using a variety of strategies. Studies which met our inclusion criteria were reviewed and data abstracted. Our outcomes of interest included: high transport status peritoneal membrane, risk for peritonitis, encapsulating peritoneal sclerosis (EPS), patient and technique survival. We combined data from studies which evaluated the same genetic polymorphism and the same outcome. Results: We evaluated 18 relevant studies. All studies used a candidate gene approach. Gene polymorphisms in the interleukin (IL)-6 gene were associated with peritoneal membrane solute transport in several studies in different ethnic populations. Associations with solute transport and polymorphisms in endothelial nitric oxide synthase and receptor for advanced glycation end product genes were also identified. There was evidence of a genetic predisposition for peritonitis found in 2 studies, and for EPS in 1 study. Survival was found to be associated with a polymorphism in vascular endothelial growth factor and technique failure was associated with a polymorphism in the IL-1 receptor antagonist. Conclusions: There is evidence that characteristics of the peritoneal membrane and clinical outcomes for PD patients have genetic determinants. The most consistent association was between IL-6 gene polymorphisms and peritoneal membrane solute transport.